pandemic and structural shifts - Grigoryeva , Elena (project baikal, 2022)
Big changes continue to invade the familiar way of life in the third year of the pandemic. Will this invasion cause changes in regulations, laws and approaches to urban development and housing design? By some indications, it may influence not only on norms and approaches, but also on the settlement system. How will the city respond to the trials caused by the virus? We present to our readers some hypotheses and assumptions of professionals, theoreticians and practitioners from Yekaterinburg, Moscow and Irkutsk.